Transformational Leadership and Innovative Behavior: Investigating The Role of Knowledge Sharing and Self-Efficacy in Indonesian Manufacturing Firms - Safitri, Wita; Sari, Kimah Amelia; Yuliawati, Yuliawati (Lentera Ilmu Nusantara, 2025)
The innovation gap in the Indonesian manufacturing sector, where only 20% of companies have adopted Industry 4.0 technology, highlights the need for leadership that fosters innovative behavior. This study examines the influence of transformational leadership on innovative behavior, with knowledge sharing as a mediating variable and self-efficacy as a moderating variable. A quantitative approach was used with 124 employees from manufacturing companies in South Cikarang selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results show that transformational leadership has a significant positive effect on both innovative behavior and knowledge sharing. Knowledge sharing also positively influences innovative behavior and mediates the relationship between transformational leadership and innovative behavior. However, self-efficacy does not significantly moderate the relationship between transformational leadership and innovative behavior. These findings underscore the importance of transformational leadership in encouraging innovation through the facilitation of knowledge exchange. Theoretically, this study contributes to the development of leadership-based innovation models by confirming the role of knowledge sharing as a key mechanism. Practically, it offers insights for organizations to enhance innovation by implementing leadership development programs and strengthening knowledge sharing systems. The study recommends that manufacturing firms invest in leadership and learning infrastructure to remain competitive in the Industry 4.0 era.